2012
DOI: 10.1155/2012/287849
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in HIV-Positive Patients: Effects on Vaginal Flora

Abstract: A high proportion of HIV-infected pregnant women present pathogenic organisms in their lower genital tract. This has been associated with the development of postpartum morbility, HIV transmission to the partner and offspring, and other gynaecological conditions, such as cervical dysplasia or cancer. Vaginal flora alterations can range from 47% in Western countries to 89% in Africa in pregnant HIV-positive patients, much higher than about 20% of the general population. Pathogen organism retrieval is high. As pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The depletion of lactobacilli may limit the production of hydrogen peroxide. Vallone et al postulated that low vaginal pH inhibits CD4 lymphocyte activation and reduces HIV target cells in the vagina, while elevated vaginal pH may enhance HIV adherence to vaginal eukaryotic cells [ 25 ]. In this present study, although BV was prevalent among both HIV positive and HIV negative, there was a significant association between BV and higher expression of HIV RNA in the plasma of HIV-infected women.…”
Section: Discussionmentioning
confidence: 99%
“…The depletion of lactobacilli may limit the production of hydrogen peroxide. Vallone et al postulated that low vaginal pH inhibits CD4 lymphocyte activation and reduces HIV target cells in the vagina, while elevated vaginal pH may enhance HIV adherence to vaginal eukaryotic cells [ 25 ]. In this present study, although BV was prevalent among both HIV positive and HIV negative, there was a significant association between BV and higher expression of HIV RNA in the plasma of HIV-infected women.…”
Section: Discussionmentioning
confidence: 99%
“…Although we matched cases and controls for potentially confounding factors, we were unable to adjust for HIV infection and hepatitis. There might be an increased prevalence of these infections among women with an abnormal vaginal flora, but it remains unclear whether this difference is related to the infection, the socioeconomic deprivation, the immunodeficiency, or to other, unknown factors [ 37 , 38 ]. Moreover, the increased susceptibility for vaginal infections in OMT women might also be induced by a frequent change of sexual partners, high sexual activity, underlying diseases, or co-abuse of other drugs that we were unable to adjust for [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…68,69 Likewise, HIV seroprevalence significantly increases in pregnant women with severe BV compared with women with lactobacilli-dominated VMB. 70,71 A prospective cohort study showed that HIV-1-seronegative women demonstrated different risks for HIV acquisition based on the presence or absence of vaginal lactobacilli. This was proposed to be based on differences in the proportion of non-H 2 O 2 -producing lactobacilli and H 2 O 2producing lactobacilli, with the latter being more beneficial in HIV prevention.…”
Section: The Vaginal Microbiome and Stismentioning
confidence: 99%
“…Cross-sectional studies have revealed that HIV is frequently correlated with BV and independent of behavioral variables associated with BV and HIV, whereas HIV infection is lower in women with vaginal eubiosis 68,69 . Likewise, HIV seroprevalence significantly increases in pregnant women with severe BV compared with women with lactobacilli-dominated VMB 70,71 . A prospective cohort study showed that HIV-1–seronegative women demonstrated different risks for HIV acquisition based on the presence or absence of vaginal lactobacilli.…”
Section: The Vaginal Microbiome and Stismentioning
confidence: 99%